2022
DOI: 10.3889/oamjms.2022.8088
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Effectiveness of Chitosan and Polysaccharide of Durian Peel Extract against Mycobacterium tuberculosis Isolates

Abstract: BACKGROUND: Tuberculosis (TB) disease is an infection caused by Mycobacterium tuberculosis and is transmitted through sputum droplets of sufferers or suspect TB in the air. Chitosan as an antimicrobial agent can be used in the biomedical field because it has a number of hydroxyl groups (OH) and amine groups (NH2). The chemical substance of durian peel extract (Durio zibethinus L.) contains pectin which is multifunctional and can be used in the pharmaceutical field. Chemically, pectin is a polysaccharide polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The results showed that the combination of snail seromucoid and chitosan has potential as a bioimmunostimulator and bioimmunodulator in TB therapy (Sutanto et al, 2020;Sutanto et al,2021a;Sutanto et al, 2021b). Durian peel extract polysaccharides and chitosan have the potential to an antimicrobial against MTb isolates (Sutanto et al, 2022).…”
Section: Effectiveness Of Atd Against Mtbmentioning
confidence: 99%
“…The results showed that the combination of snail seromucoid and chitosan has potential as a bioimmunostimulator and bioimmunodulator in TB therapy (Sutanto et al, 2020;Sutanto et al,2021a;Sutanto et al, 2021b). Durian peel extract polysaccharides and chitosan have the potential to an antimicrobial against MTb isolates (Sutanto et al, 2022).…”
Section: Effectiveness Of Atd Against Mtbmentioning
confidence: 99%